Arthrodesis or Open Reduction Internal Fixation for Lisfranc Injuries: A Meta-analysis. Issue 2 (April 2022) - Levy, Christopher J.; Yatsonsky, David; Moral, Muhammad Z.; Liu, Jiayong; Ebraheim, Nabil A.
The purpose of this study is to determine if arthrodesis, compared with open reduction and internal fixation (ORIF), produces favorable American Orthopaedic Foot and Ankle Society (AOFAS) and visual analogue scale (VAS) scores, and to determine if differences in complication, revision surgery, and secondary arthrodesis rates exist for patients with Lisfranc fracture/dislocation injuries. Searches were performed in PubMed using the keywords "Lisfranc fracture, " "metatarsal fracture, " "ORIF, " "open reduction internal fixation, " "arthrodesis, " and "fusion." These criteria left 183 articles for review. Exclusions left 21 articles and 2 translations of Chinese abstracts. Data analysis was performed using Student's 2-sample t test for samples of equal variance, and chi-square test for goodness of fit. The t test revealed a significant difference ( P = .03) between the average AOFAS score for patients who underwent primary arthrodesis (84.7 ± 6.14) compared with those who were treated with ORIF (78.9 ± 5.09). There was no significant difference for the average VAS scores ( P = .33) of the arthrodesis and ORIF groups. The complication rate of arthrodesis patients was significantly lower than ORIF patients ( P = .04), and the rates of revision surgery ( P = .22) and secondary arthrodesis ( P = .53) were not significant between the groups. The results of this study indicate that arthrodesis may be a better surgical option than ORIF, due to the higher functional scores and the lower complication rate. Levels of Evidence: Level III: A meta-analysis